Coping strategies in young men with and without drinking problems. - Fradet, Christiane. (University of Ottawa (Canada), 1993)
Social learning theory (Abrams & Niaura, 1987) assumes that individuals who lack effective coping strategies are more likely to drink in response to stressful situations. A review of the literature suggests that coping strategies have not typically been studied in the context of a specific theory of alcohol abuse. Consequently, little progress has been made in the understanding of possible links between alcohol abuse and the use of coping strategies. The primary objective of the present study was to assess whether drinking problems are associated with specific coping strategies. Coping strategies were defined according to the coping models of Lazarus and Folkman (1984), Tobin, Holroyd, Reynolds and Wigal (1989) and Rosenbaum (1980). It was hypothesized that students with drinking problems, in comparison to students with no drinking problems, would report engaging less in self-control and problem-focused strategies and more in avoidant coping strategies. A secondary objective was to determine whether these coping characteristics are associated with a family history of drinking problems, a risk factor for drinking problems. One hundred and eighty-nine male university students completed screening questionnaires about their alcohol and drug consumption and about the drinking behaviors of their family members. Students accepted for this study met the criteria for one of the following groups: (a) no family history of drinking problems (FH$-$) and no drinking problems, (b) FH$-$ and drinking problems, (c) family history of drinking problems (FH+) and no drinking problems, or (d) FH+ and drinking problems. Students completed self-report questionnaires on the reactions they experience in stressful situations. Self-control strategies were assessed by the Self-Control Schedule (Rosenbaum, 1980), and task-oriented and avoidant strategies by the Coping Inventory for Stressful Situations (Endler & Parker, 1990a). The last questionnaire was repeated for three different situations: (a) negative emotion, (b) interpersonal conflict, and (c) pressure to drink. Multivariate analyses of variance showed that students with drinking problems, in comparison to students without drinking problems, reported engaging less in self-control and task-oriented coping strategies. However, students with drinking problems did not report engaging more in avoidant strategies. This finding was contrasted with the results of other studies in which avoidant strategies were found to be related to alcohol abuse. Finally, there were no significant differences in coping between FH+ students and FH$-$ students. The potential relevance of coping to a model of alcohol abuse was discussed as well as its practical implications. For example, students with drinking problems might benefit from being taught task-oriented strategies and self-control skills, in addition to specific skills to reduce drinking.
Keywords: Psychology, Clinical.